The British-Irish Border in the Context of Brexit - Balawajder, Grzegorz (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The subject of the paper is reflections on the consequences of Brexit for the functioning of the border between Ireland and Northern Ireland. The author explains what this border means when the United Kingdom is no longer a member of the European Union, and thus the border may be a barrier to the free movement of people, goods, capital and services. At the same time, it is stressed that the exit of the United Kingdom from the European Union will have a significant impact on the change of the function of this border, which from then on is no longer an internal border of the Union. The aim of the paper is therefore to analyse the consequences of this change, with a simultaneous indication of different models of the UK’s functioning with relation to the European Union and their impact on the British-Irish relations, especially with regard to the various dimensions of the border as a barrier. The article presents various scenarios of solutions that will determine their mutual relations as a result of negotiations between the European Union and Great Britain, especially with regard to access to the single European market, which in turn will be influenced by the border between Ireland and Northern Ireland in the scope of the free movement of people, goods, capital and services. The author used the system analysis method and the comparative method. The author puts forward the thesis that if the negotiations cause a fairly strong loosening of relations between the UK and the European Union, to mitigate the consequences of such a situation for the Irish-British relations, it will be necessary to find and develop bilateral solutions that will facilitate border crossing. The Smart Border 2.0 concept can constitute such a solution.

Przedmiot artykułu stanowią rozważania dotyczące konsekwencji Brexitu dla funkcjonowania granicy pomiędzy Irlandią a Irlandią Północną. Autor wyjaśnia, czym jest ta granica w warunkach, kiedy Wielka Brytania nie jest już członkiem Unii Europejskiej, a więc przebieg tej granicy może stanowić barierę dla swobodnego przepływu osób, towarów, kapitału i usług. Artykuł jednocześnie podkreśla, że wyjście Wielkiej Brytanii z Unii Europejskiej będzie miało istotny wpływ na zmianę funkcji tej granicy, która od tej chwili nie będzie już wewnętrzną, lecz zewnętrzną granicą Unii. Celem artykułu jest zatem analiza konsekwencji tej zmiany z równoczesnym wskazaniem różnych modeli funkcjonowania Wielkiej Brytanii względem Unii Europejskiej oraz ich wpływu na relacje brytyjsko – irlandzkie, szczególnie w odniesieniu do różnych wymiarów przejawiania się granicy, jako bariery. Autor zastosował metodę analizy systemowej i metodę porównawczą. Artykuł wskazuje na różne możliwe scenariusze rozwiązań, jakie w wyniku negocjacji pomiędzy Unią Europejską a Wielką Brytanią określą ich wzajemne relacje, szczególnie w odniesieniu do dostępu do jednolitego rynku europejskiego, czego z kolei implikacją będzie oddziaływanie granicy pomiędzy Irlandią a Irlandią Północną w zakresie swobody przepływu osób, towarów, kapitału i usług. Autor stawia tezę, że w przypadku, jeśli negocjacje spowodują dość mocne rozluźnienie związków Wielkiej Brytanii z Unią Europejską, to dla złagodzenia skutków tej sytuacji dla relacji irlandzko – brytyjskich istnieje konieczność znalezienia i wypracowania bilateralnych rozwiązań, które ułatwią przekraczanie granicy. Takim rozwiązaniem może być koncepcja Smart Border 2.0.
Granica brytyjsko-irlandzka w kontekście Brexitu
Keywords: Brexit; border between the Republic of Ireland and Northern Ireland; Common Travel Area; European union; internal Union border; external border of the Union; border functions; Brexit; granica pomiędzy Republiką Irlandii a Irlandią Północną; Wspólny Obszar Podróży; Unia Europejska; granica wewnętrzna Unii; granica zewnętrzna Unii; funkcje granicy